MECHANISM OF STATE REGULATION OF LAND USE PROCESSES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the peculiarities of the mechanism of state regulation of land use processes. Groups of social, ecological and economic aspects have been studied. It is emphasized that the regulation of economic processes of land use is impossible without reliable information about the qualitative characteristics of each specific plot, its economic and biological fertility, because ignoring or incorrect assessment of its potential can negate the results of planning, which is one of the main functions of management.By the economic aspects of land use, we primarily understand  transferability as a property of a land plot, expressed in its ability to be freely alienated or transferred from one person to another in the order of universal legal succession or in another way; forms of ownership and management characterizing legal issues of land use, as well as organizational and technological conditions of agricultural production; the value of land resources as a measure of materialized labor necessary to support sustainable and effective development of agricultural production.Selected aspects of land use regulation formed the basis of the structural diagram of the mechanism of state regulation of land use processes presented by us and allow not only to clarify its content, but also directly determine its structure.It was determined that in the conditions of market relations, an important place in the system of state regulation of land use began to be assigned to the cadastral assessment of land plots. The content of the use of the land resource potential of the territorial formation is given.In the regulation structure, special attention should be paid to the issue of comprehensive assessment of the effectiveness of the use of land resources and the resulting need for further development of the methodological base for the assessment of land use.The key link in the process of state regulation should be the evaluation of the efficiency of land use, which is based on a system of quantitative parameters for the evaluation of the efficiency of the use of land resources.Land owners are mainly municipal authorities, enterprises (legal entities), citizens (individuals) or their associations (cooperatives, commercial firms, etc.).The denationalization of land ownership and the introduction of private land ownership on this basis, the privatization of land, the introduction of paid land use fundamentally changed the structure and content of land relations in the conditions of village land use, changed the structure, content and principles of planning land resource formations.The effective organization of state regulation of economic processes of land use has a significant impact on the process of creating the necessary organizational, territorial, legal and social conditions for full involvement in turnover, increasing the return of each hectare of land while preserving or reproducing soil fertility.
Keywords: state regulation, land relations, balanced land use, economic processes of regulation, natural resources, cadastral assessment.